Chemical analysis on the honey of Heterotrigona itama and Tetrigona binghami from Sarawak, Malaysia - Wong, Pearly; Hii, Siew Ling; Koh, Chen Chung; Moh, Thomas Shan Yau; Suzy Rini Gindi, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study aims to compare the chemical composition of honey samples produced by Heterotrigona itama and Tetrigona binghami which originated from Sarawak, Malaysia. One hundred and six (106) honey samples were collected from local bee farms and analysed in terms of their chemical profiles. The chemical analysis conducted includes physicochemical composition such as moisture, total phenolic content, sugar, 5-hydroxymethylfurfural (5-HMF), pH and organic acids and proximate analysis which included ash, protein, carbohydrates and energy. Independent T-test was used as a statistical tool to investigate the significant difference between the composition of both honey samples. The results showed that honey samples of Heterotrigona itama and Tetrigona binghami possessed significant difference (p<0.05) in moisture, total phenolic content, fructose, glucose, pH, protein, gluconic acid, acetic acid, ash, carbohydrates and energy. The honey samples of Heterotrigona itama exhibited significantly higher fructose and glucose at the average of 22.00 ± 3.48 g/ 100 g and 23.45 ± 3.23 g/100 g, respectively. Besides, the honey samples also possessed higher pH value, gluconic acid, ash, carbohydrates and energy. Meanwhile, Tetrigona binghami honey samples possessed significantly (p< 0.05) higher moisture content, total phenolic content, protein and acetic acid compared to the Heterotrigona itama’s honey samples. To conclude, the geographical and floral origins of honey are the two important quality parameters which fundamentally affect the physical-chemical properties as well as biological activities of honey samples.